Cryptocurrency market dynamics: analysis of price movements and their influence factors - Nugrahani, Wahyu Panji; Pratiwi, Leni Nur; Yanida, Pebri (Jurnal Ekonomi, 2024)
This article analyzes cryptocurrency market dynamics with a special focus on price movements and the factors that influence them. We explore high market volatility, highlighting price movement trends in the long and short term. Our analysis includes technical aspects, such as moving averages, RSI, and MACD indicators, to help understand market patterns and momentum. We also consider fundamental factors, including trading volume, market sentiment, and the impact of economic news on price changes. The results of the regression analysis show that trading volume has a significant correlation with price movements, reflecting the critical role of market participation in determining price direction. Market sentiment and global economic events have also been shown to significantly influence price fluctuations, demonstrating the extent to which market information and perception can be a catalyst for price change. In addition, we identify intraday factors that play an important role in cryptocurrency price movements in the short term. This article provides in-depth insight into the complexity of cryptocurrency market dynamics and contributes to the understanding of those concepts that have not been fully uncovered in previous literature. The results of this research can provide valuable guidance for investors, market analysts, and regulators to make smarter investment decisions in the face of this unique market volatility.